Antibiotic prophylaxis in the management of percutaneous endoscopic gastrostomy in infants and children - Engelmann, Guido; Wenning, Daniel; Fertig, Eduard; Hoffmann, Georg F.; Teufel-Schäfer, Ulrike (Pediatrics international, 2015)
Background In randomized controlled trials in adult patients the use of prophylactic broad-spectrum antibiotic reduces the number of insertion site and systemic infections, associated with placement of percutaneous endoscopic gastrostomy (PEG) tubes. For pediatric patients no such trials exist. The aim of this study was to assess the value of antibiotic prophylaxis in PEG placement in pediatric patients. Methods In a retrospective chart review PEG placement in infants and children performed in a tertiary care center was analyzed. All PEG procedures were performed by an experienced pediatric gastroenterologist using the pull-through technique under general anesthesia. Results A total of 103 procedures were analyzed; 33 patients received antibiotic prophylaxis and 70 did not. Two (6%) of the patients receiving prophylaxis developed local or systemic infections after PEG placement, whereas seven (10%) without prophylaxis suffered from a PEG-related infection. This difference was not significant on chi-squared test (P = 0.5). Sixty patients had a body temperature >38°C within the first 3 days after the PEG procedure. A total of 77% of these patients had no antibiotic prophylaxis. Mean body temperature differed significantly between patients with and without prophylaxis (37.9°C vs. 38.3°C, respectively; P = 0.02). Conclusions The incidence of PEG-related local or systemic infection after PEG-placement was not significantly different between patients with and without antibiotic prophylaxis, but the latter had a significantly higher mean body temperature after the PEG procedure. Taking elevated mean body temperature as a marker for putative bacteremia it is suggested that antibiotic prophylaxis is indicated in all pediatric patients after PEG placement.